Oxaliplatin-Induced Leukocytoclastic Vasculitis under Adjuvant Chemotherapy for Colorectal Cancer: Two Cases of a Rare Adverse Event - Henriette Quack (Case Reports in Oncology, 2013)
Leukocytoclastic vasculitis is a multicausal systemic inflammatory disease of the small vessels, histologically characterized by inflammation and deposition of both nuclear debris and fibrin in dermal postcapillary venules. The clinical picture typically involves palpable purpura of the lower legs and may be associated with general symptoms such as fatigue, arthralgia and fever. Involvement of the internal organs, most notably the kidneys, the central nervous system or the eyes, is possible and determines the prognosis. Oxaliplatin-induced leukocytoclastic vasculitis is a very rare event that limits treatment options in affected patients. We report 2 patients who developed the condition under chemotherapy for advanced rectal and metastatic colon carcinoma, respectively; a termination of the therapy was therefore necessary. While current therapies for colorectal cancer include the combination of multimodal treatment with new and targeted agents, rare and unusual side effects elicited by established agents also need to be taken into account for the clinical management.